Optimizing Ballistic Schemes for Transfer to Geostationary Orbits by Electric Propulsion. (2017) - Salmin, V.V.; Petrukhina, K.V.; Chetverikov, A.S.
Abstract: The problem of the choice of optimal ballistic schemes for a transfer to a geostationary orbit (GEO) with low and high thrust propulsion is considered. A bi-criteria optimization problem is solved by outputting a set of Pareto-optimal solutions. Results of the numerical modeling of combined insertion schemes, their ballistic optimization, and calculations of design parameters for a spacecraft with a combined propulsion unit are given. To insert a satellite into a given orbital plane, semi-major axis and eccentricity deviations are reduced by solving a terminal control problem. An approximately-optimal control and an expression for characteristic velocity expense as a function of initial boundary conditions with insertion of an electric propulsion (EP) powered spacecraft into a given station with the control are obtained.